Modeling reactive flow on carbonates with realistic porosity and permeability fields. (May 2020) - de Paulo Ferreira, Leandro; Surmas, Rodrigo; Tonietto, Sandra Nelis; da Silva, Mônica Antunes Pereira; Peçanha, Ricardo Pires
Highlights: A methodology for calculating porosity field from micro-CT images in heterogeneous carbonates. Two methodologies for estimating permeability fields in heterogeneous carbonates by using micro-CT images and Direct Numerical Simulations. Carbonate heterogeneity reproduced in porosity and permeability fields. Carbonate acidification by CO2 and HCl simulated by a two-scale continuum solver. Simulations allowed prediction of permeability curve and wormhole path resulted from acidification process. Abstract: CO2 reinjection in petroleum reservoirs brings advantages in oil production but may cause dissolution in carbonate reservoirs. Two-scale continuum models have been successfully used to simulate acidification. However, the use of realistic porosity and permeability fields in mesh simulations is still a challenge, in such a way that uniform and normal distributions have been used to generate these fields in the past. The main objective of this work was to transcript the plugs heterogeneity from the micro-CT images to simulation. The porosity field was calculated directly from micro-CT images, and two methodologies are proposed to calculate the permeability field. A reactive two-scale continuum solver was implemented in OpenFOAM and used to simulate reactive flow in two carbonate samples with different intrinsic reaction rates (calcite and dolomite). The experimental permeability evolution curves, as well as wormholes shapes and paths, are reproduced in the simulations. We observed a critical influence of specific surface area, reaction rate constant, and initial permeability field for the simulations of acidification processes.